Perceptions of preventing premarital sex among adolescents on Islamic campus - Waliyanti, Ema; Wulandari, Dwi (Journal of Health Technology Assessment in Midwifery, 2023)
Background: Adolescents are curious, challenge themselves, and take risks. Unstable adolescent self-control, lack of knowledge, and lack of faith make adolescents susceptible to premarital sex. Purpose: To explore perceptions of preventing premarital sex among adolescents on an Islamic campus. Method: This study used a qualitative approach with descriptive methods. Data collection through in-depth interviews using an interview guide with 7 students identified through purposive and maximum variation sampling. Validity testing of the data using member checks, peer debriefing, and thick descriptions. Thematic analysis was carried out using Open Code 4.02 software. Results: Students perceive premarital sex as sex before marriage, kissing, holding hands, and hugging, which can have physical, psychological, academic, and social consequences. The causative factors are lust, food, environment, and knowledge. Premarital sex can be prevented by oneself, religion, campus, education, and parents. Premarital sex can be dealt with by regulation and institutional treatment. Islam considers premarital sex unlawful, and students on Islamic campuses do not necessarily abstain from premarital sex. This perception is influenced by culture, experience, and history of information. Conclusion: Perception will influence students' behavior towards premarital sex, so they need to have good knowledge and self-control to avoid premarital sex behavior.